(untitled) (Historia, 2021)
In July 1810, a Gonaqua woman bearing the colonial name Sara Baartman, arrived in England after a journey that brought her to Europe from her native southern Africa. After spending five years on display on European stages in England and France as the “Hottentot Venus”, Sara passed away at the end of 1815 in Paris. In January 1816, one of Europe’s foremost scientists, Georges Cuvier, dissected the remains of Sara Baartman. Cuvier concluded in his study published in 1817 in the Histoire naturelle des mammiferes – a volume about the studies of mammals in which Baartman was the only human represented – that the “Hottentot” body was more closely related to the great apes than to the human species. A cast was made of Baartman’s body; her skeleton, genitals and brain were removed and preserved and subsequently displayed at the Musée de l’Homme in Paris until the 1970s. In 1995, the Griqua National Conference, led by genealogist Mansell Upham, approached the newly elected post-apartheid South African government to have the remains of Sara Baartman returned to South Africa. Upham perceived in Baartman “the plight of indigenous people, and a story of dehumanisation and the tragedies befalling black women in colonial societies”. For Upham, the call to return Baartman’s remains “appealed to a shared aboriginal past amongst South Africans of all races in attempts to reclaim an almost forgotten Khoekhoe/San heritage”.After five years of failed negotiations, former Khoekhoe/San heritageentered into direct negotiations with thein 2000, and on May 2002 Baartman’s remains arrived in Cape Town. According to then Minister of Arts and Culture, Bridgette Mabandla, Baartman’s return to South Africa symbolised the return of African cultural heritage from Europe and thus an end to colonialism as well as illustrating her importance to a large majority of South Africans. After a great deal of consideration, Baartman was buried in the small farming town Hankey in the Eastern Cape on 9 August 2002 – National Women’s Day.